Copper nanoparticles modified graphitic carbon nitride nanosheets as a peroxidase mimetic for glucose detection. Issue 111 (26th October 2015) - Wang, Nan; Han, Zhenwei; Fan, Hai; Ai, Shiyun
Abstract : Cu NPs/g-C3 N4 was successfully prepared by the calcination of dicyandiamide–Cu 2+ complex as a peroxidase mimic for sensitive detection of glucose. Abstract : In this study, copper nanoparticles modified graphitic carbon nitride nanosheets (Cu NPs/g-C3 N4 ) as a novel peroxidase mimetic were successfully prepared by the calcination of dicyandiamide–Cu 2+ complex with the assistance of humic acid. The morphology and structure of the product were characterized by X-ray powder diffractometry (XRD), Fourier transform infrared spectroscopy (FTIR) and transmission electron microscopy (TEM). The prepared Cu NPs/g-C3 N4 was found to have highly peroxidase-like activity, which can rapidly catalyze the oxidation of peroxidase substance 3, 3′, 5, 5′-tetramethylbenzidine (TMB) to produce a blue color in the presence of H2 O2 . Accordingly, a simple, selective and fast colorimetric method was developed for H2 O2 and glucose detection. The prepared Cu NPs/g-C3 N4 exhibited low detection limits of 3.2 × 10 −8 M and 3.7 × 10 −7 M for H2 O2 and glucose, respectively, due to the excellent peroxidase-like activity of Cu NPs/g-C3 N4 originating from the synergistic effect of Cu NPs and g-C3 N4 . In this work, we utilized the easily forming complex ability of dicyandiamide and Cu 2+ ions to form a homogeneous precursor solution, and then obtained the CuNPs/g-C3 N4 product; such a method may have wide applications in novel composite nanomaterial preparation. The product may have promising applications in medical diagnostics and biotechnology fields.